A comprehensive study of routing protocols for cognitive radio networks - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Mahmoud, Omer (Little Lion Scientific Islamabad Pakistan. Also Available via libraries of EBSCO Publishing USA., 2013)
The rapid development of wireless communication technologies results in the problem of radio spectrum shortage. Additionally, the traditional fixed spectrum allocation scheme can lead to the significant spectrum underutilization. Cognitive radio (CR) is an emerging technology to solve those problems by enabling unlicensed users to opportunistically access the available licensed bands in an intelligent and cautious manner. In cognitive radio networks (CRNs), the data routing is one of the most important issues to be taken into account and requires more study. This paper surveys recent routing protocols for CRNs and introduces the classification of routing techniques as well as presenting significant challenges which need to be considered for routing design. The main purpose of this survey is to provide a comprehensive and critical study on the current routing schemes in order to expose new open issues as well as being utilized to either improve the existing routing techniques or to develop new routing solutions. The possible future research in routing for CRNs is also given.